GUARANTEES TO PROVIDE SOCIAL PROTECTION AND LIVING CONDITIONS FOR THE POPULATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Social protection of the population is one of the main forces of the development of our society, the level of living standards of the population and social stability, equal rights, differences between our people, employment of the population, and the implementation of a number of programs and reforms implemented by our state to improve the lives of the poor, needy and those in need of social protection are reflected.